A deficit in using prosodic cues to understand communicative intentions by children with autism spectrum disorders: An eye-tracking study. Issue 1 (February 2020) - Zhou, Peng; Ma, Weiyi; Zhan, Likan
The present study investigated whether Mandarin-speaking preschool children with autism spectrum disorders (ASD) were able to use prosodic cues to understand others' communicative intentions. Using the visual world eye-tracking paradigm, the study found that unlike typically developing (TD) 4-year-olds, both 4-year-olds with ASD and 5-year-olds with ASD exhibited an eye gaze pattern that reflected their inability to use prosodic cues to infer the intended meaning of the speaker. Their performance was relatively independent of their verbal IQ and mean length of utterance. In addition, the findings also show that there was no development in this ability from 4 years of age to 5 years of age. The findings indicate that Mandarin-speaking preschool children with ASD exhibit a deficit in using prosodic cues to understand the communicative intentions of the speaker, and this ability might be inherently impaired in ASD.